Reformoptionen des Länderfinanzausgleichs unter politökonomischer Betrachtung - Michael Broer (Wirtschaftsdienst, 2014)
Bayern und Hessen haben im März 2013 eine Klage vor dem Bundesverfassungsgericht gegen das Gesetz über den Länderfinanzausgleich eingereicht. Reformvorhaben müssen aber auch politische Mehrheiten im Bundestag und Bundesrat erreichen. Allein aus politökonomischer Perspektive erscheint eine Reform der in der Verfassungsklage thematisierten Regelungen nicht möglich. – – The German states Bavaria and Hesse have initiated a legal case against the German fiscal equalisation system. The German Federal Constitutional Court has already made rulings concerning this system on three occasions, and thus this new case is not expected to result in major changes. Consequently, states may have to depend on the Bundestag and Bundesrat to implement any changes to the system. Minor reforms would be likely to pass muster with the Court. This is important, as even minor changes can have a significant impact on states' revenues. This study analyses whether there are policy reform options that could attain majorities in the Bundestag and Bundesrat and estimates the possible effects of the policies on states' revenues.
Keywords: H70; H77; 330; Länderfinanzausgleich; Finanzbeziehungen; Reform; Deutschland